TRAINING AND ASSISTANCE OF FOOD VENDORS IN EFFORTS TO PREVENT FOODBORNE DISEASES IN KENJERAN VILLAGE SURABAYA - Fariani Syahrul; Annis Catur Adi; Riris Diana Rachmayanti; Kartini Kartini (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Based on the results of research in 2020 in the Kenjeran village, bacterial contamination was identified in food and snacks sold around homes and schools. The results of laboratory tests identified that 51.35% of snacks were contaminated with bacteria, with details of 32.43% contaminated with potential pathogenic Escherichia coli bacteria and 45.54% contaminated with Klebsiella pneumonia bacteria. Objective: This activity aims to increase the knowledge of food vendors in terms of managing snacks and reduce the number of percent snacks that contaminated with microbes. Methods: The main activities were the training of food and beverage management and cadre assistance that held after training to see changes in the behavior of food vendors and laboratory tests to see percent of snacks containing microbial contamination. Results: There was no difference in food vendors' knowledge of snacks management before and after training, and 72.8% of snacks contained bacteria, but the cleanliness and hygiene behavior of food vendors were increased. Conclusion: This activity has provided increased awareness about safe and healthy food and beverage management practices to food vendors around the site but there are still many snacks that contain microbes even increased from the results of last year's study. Suggestion that there is registration for food vendors so that mentoring activities can be carried out continuously by cadres and villages related to food management at food vendors around Kenjeran village.